Pelatihan Kesenian Tradisional Pabitte Pasappu Untuk Pemertahanan Budaya Masyarakat Kajang di Desa Tanah Toa, Bulukumba, Sulawesi Selatan: The Traditional Performance of Pabitte Pasappu Training for Preservation of the Kajang Community Culture in Tanah Toa Village, Bulukumba, South Sulawesi - Rabani, La Ode; Husain, Sarkawi B.; Samidi, Samidi; Khusyairi, Johny Alfian (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Local Society make the preservation of local arts and culture. One of the local communities that is the focus of community service is the Kajang indigenous community in Bulukumba, South Sulawesi. The Kajang community carries out its activities separately between Inner and Outer Kajang. Both spaces of communities have different standards in preserving one cultural art. The Inner Kajang community focuses on sacred traditional arts, while in the Outer Kajang community, the inherent traditions are profane. This community service is directed towards the goal of preserving/sustainability of the local culture of the Kajang community, which is being threatened by the influence of globalization, the influence of digital technology that enters the community, and the orientation of the Kajang Society which likes the world of modernity. As a result, sacred and profane traditional arts not attention, especially from the local younger generation. The method of community service is through training the younger generation of the Kajang community who come from the local community. Pabitte Pasappu Art Trainers come from local traditional leaders. This dedication succeeded in training the young generation of Kajang in an effort to maintain their art Pabitte Pasappu. The successful performance as shown on the YouTube channel of Prodi Ilmu Sejarah Unair became a benchmark for the success of this community service program, although in the not too distant future. The effectivity, time efficiency and intensity during training are key to achieving training targets.